2004
DOI: 10.1038/sj.ijo.0802802
|View full text |Cite
|
Sign up to set email alerts
|

Role of television in childhood obesity prevention

Abstract: OBJECTIVE:To assess the role of television as tool for childhood obesity prevention. METHOD: Review of the available literature about the relationship between television and childhood obesity, eating habits and body shape perception. RESULTS:The reviewed studies showed the following: television watching replaces more vigorous activities; there is a positive correlation between time spent watching television and being overweight or obese on populations of different age; obesity prevalence has increased as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
1
17

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 33 publications
3
85
1
17
Order By: Relevance
“…[7][8][9][10][11] This increased consumption is of concern to the health profession and may reflect extensive advertising of sweet drinks during children's television shows in many countries, including Australia. 4,[12][13][14][15][16] The beverage industry has reported increased sales of bottled water, 17 but there are no data to indicate children are drinking this in preference to tap water. Anecdotal reports linking increased caries prevalence and bottled water consumption are speculative.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] This increased consumption is of concern to the health profession and may reflect extensive advertising of sweet drinks during children's television shows in many countries, including Australia. 4,[12][13][14][15][16] The beverage industry has reported increased sales of bottled water, 17 but there are no data to indicate children are drinking this in preference to tap water. Anecdotal reports linking increased caries prevalence and bottled water consumption are speculative.…”
Section: Introductionmentioning
confidence: 99%
“…Excess body weight negatively impacts self-esteem, social and cognitive development (2) , and leads to a spectrum of comorbidities including type 2 diabetes, CVD and multiple cancers that reduce quality of life, life expectancy, and cost billions of dollars in health-care spending (3)(4)(5) . Multiple cross-sectional and longitudinal studies have shown that increased television viewing is associated with an increased risk of obesity in children (6)(7)(8)(9)(10) . Except sleep, children spend more time watching television than doing any other single activity (11) .…”
mentioning
confidence: 99%
“…Several mechanisms may underlie the positive association between television viewing and obesity. Television watching is sedentary and replaces more vigorous activities, leading to a decline in energy expenditure (10) . Another suggested mechanism is the influence of food advertisements on food choices and nutrition.…”
mentioning
confidence: 99%
“…21 This information would influence the choice of foods. Major proportion of food ads during the most popular sessions were sugarsweetened beverages and fast foods.…”
Section: Children's Dietary Habitsmentioning
confidence: 99%
“…17 Scientists reviewed previous studies, and found TV viewing gradually occupied time of active activities. 21 As to recommendation in TV viewing, research suggested 2 hours as an indicator to predict unhealthy dietary habit and physical inactivity. Because the time spent on TV view would overlap the time spent on physical activity, "Healthy People 2010" set the physical activity goal of children and adolescents as "more than 75% children and adolescents watch TV less than 2 hours in a day".…”
Section: Children's Sedentary Activitiesmentioning
confidence: 99%